Needs Analysis of Developing Innovative Materials in Translation Course at Vocational Higher Institution - Miladiyenti, Fithratul; Laily, Hamidah Izzatu; Ramadhani, Astuti Pratiwi (Politeknik Negeri Padang, 2024)
In a rapidly interconnected world, where the demand for cross-cultural communication continues to grow, the significance of qualified translators remains crucial. To meet this demand, there is a need to explore innovative ways of designing effective teaching and learning materials for translation courses, including in the English Department, Politeknik Negeri Padang. This study aims to investigate the significance of developing innovative materials adapted to the unique needs of the translation classroom. In this study, two perspectives were applied, considering both the students’ perspectives and the professional translators’ perspectives, as experts. The study was part of an R&D study utilizing mixed approaches, incorporating observation, interviews, and questionnaires to ensure comprehensive and insightful results. The collected data was then descriptively analyzed. Through the needs analysis, the study contributes to the enhancement of the quality of information during the development of innovative materials to cultivate a new generation of competent translators.